Perancangan Sistem Informasi Reservasi Online Pada Anfadptr Hotel - AAN FADILLAH PUTRA ahmad (STKIP Taman Siswa Bima, 2024)
Hotel reservation activities that are carried out manually or do not involve technology make the management process slow and ineffective. This means that hotels will manage reservations through pen and paper, notebooks, telephone calls, face to face, or other physical means that are considered no longer in accordance with the current era. Building an effective and efficient management system is the goal of designing this system to ensure that hotel management will never experience data loss again. Therefore, it is very important to examine the shortcomings of the previous management system (manual). In addition, the author will seek solutions to the shortcomings of the previous management system (manual). The challenge,